Synthesis of the reported protoberberine gusanlung D - Wakchaure, Prasad B.; Easwar, Srinivasan; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from homopiperonylamine or phenethylamine with homophthalic anhydride or 3,4-methylenedioxyhomophthalic acid, respectively, facile syntheses of the reported structures of (+/-)-gusanlung D and (+/-)-isogusanlung d were accomplished via regioselective reductive dehydration of the corresponding homophthalimides followed by an intramolecular acid-catalyzed or radical cyclization pathway. Starting from the corresponding suitably ortho-halogenated homophthalimides, the syntheses of dehydrogusanlung and dehydroisogusanhing D were completed via regioselective reductive dehydration followed by an intramolecular Heck coupling reaction as the key steps. The analytical and spectral data obtained for all four synthetic compounds differed from the reported data for natural gusanling D, and therefore the structural assignment of the natural product needs to be revised.
Keywords: gusanlung D; Heck reaction; homophthalic anhydride; homopiperonyl amine; reductive dehydration